The cardiovascular risk of celecoxib for knee osteoarthritis: A protocol for systematic review and meta-analysis - Cheng, Shirui (Medicine (Baltimore), 2020)
OBJECTIVE: The aim of this systematic review and meta-analysis is to assess the cardiovascular (CV) risk of celecoxib on knee osteoarthritis (KOA) patients compared with the risk in those prescribed other non-selective non-steroidal anti-inflammatory drugs (NSAIDs), no intervention or placebo-controlled patients. METHODS: The following databases will be searched: MEDLINE, EMBASE, the Cochrane Library, Web of Science, Chinese Biomedical Literature Database, Chinese Nation Knowledge Infrastructure, Wanfang Database, and the Chongqing VIP from inception to April 1, 2020. All randomized controlled trials (RCTs) of celecoxib that presented data on serious cardiovascular events among KOA patients will be included. Study selection, data extraction, quality assessment, and assessment of risk bias will be performed by 2 reviewers independently. Odds ratios and correlative 95% confidence intervals will be calculated to present the association between the celecoxib and CV risk using Review Manager version 5.3 when there is sufficient available data. ETHICS AND DISSEMINATION: This review does not require ethical approval. The results of this review may be published in a peer-reviewed journal or disseminated at relevant conferences. PROSPERO REGISTRATION NUMBER: CRD42020166721.